Brain-computer interfaces - Amstutz, Lisa J. (Science for the future (Focus Readers (Firm)), 2020)
Examines the history, development, and uses of brain-computer interfaces (BCIs). Also describes the challenges of this technology and how it could be used in the future. Includes a quiz, color photographs, a glossary, and further resources.